Kontribusi Trait Kepribadian terhadap Psychological Well-Being pada Komunitas Lansia “X” di Kota Bandung - Juliyanti Juliyanti (Universitas Kristen Maranatha, 2018)
The purpose of this study was to build mental awareness of the psychological well-being of the elderly in the elderly community